2007
DOI: 10.1242/jeb.008391
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial acclimation: sex specific thermal acclimation of metabolic capacity in the striped marsh frog (Limnodynastes peronii)

Abstract: SUMMARY Reproductive success in thermally varying environments will depend on maintaining metabolic capacity of tissues that are important in mating behaviours. Here we test the hypothesis that cold acclimation will occur in those tissues that are important for reproduction, and that acclimation will be sex specific, reflecting behavioural differences between the sexes. We used the frog Limnodynastes peronii as a model because anurans engage in energetically demanding reproductive behaviour, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Diet and prandial state are widely recognized as influencing physiological processes (Wang et al, 1995;McCue, 2006;Secor, 2009). Gender, whether through sexual dimorphism or the hormonal differences between males and females, can have major influences on the physiology of experimental animals (Czerniak, 2001;Orlando and Guillette, 2007;Rogers et al, 2007;Shen et al, 2011). The enormous effect on metabolism in animals that undergo night-time torpor (Schleucher, 2004;Heldmaier et al, 2004;Swoap, 2008) or seasonal hibernation (Geiser, 2004;Drew et al, 2007;Storey and Storey, 2010;Jackson and Ultsch, 2010) also makes time of day and season key factors.…”
Section: Sources Of Physiological Variation -The 'Usual Suspects'mentioning
confidence: 99%
“…Diet and prandial state are widely recognized as influencing physiological processes (Wang et al, 1995;McCue, 2006;Secor, 2009). Gender, whether through sexual dimorphism or the hormonal differences between males and females, can have major influences on the physiology of experimental animals (Czerniak, 2001;Orlando and Guillette, 2007;Rogers et al, 2007;Shen et al, 2011). The enormous effect on metabolism in animals that undergo night-time torpor (Schleucher, 2004;Heldmaier et al, 2004;Swoap, 2008) or seasonal hibernation (Geiser, 2004;Drew et al, 2007;Storey and Storey, 2010;Jackson and Ultsch, 2010) also makes time of day and season key factors.…”
Section: Sources Of Physiological Variation -The 'Usual Suspects'mentioning
confidence: 99%
“…Lactate dehydrogenase is a glycolytic enzyme that converts pyruvate to lactic acid, thereby producing ATP rapidly in the absence of oxygen. All assays were conducted at 15 and 25°C according to published protocols (Rogers et al, 2007).…”
Section: Metabolic Enzyme Activitiesmentioning
confidence: 99%
“…For P. ridibundus and L. catesbeiana, mitochondrial oxygen consumption and membrane potential were assayed at 25°C. For R. temporaria, mitochondrial oxygen consumption and membrane potential were assayed at 20°C (values are from Salin et al, 2012b) and corresponding values were recalculated to 25°C assuming a Q 10 of 2.3 for oxygen consumption and of 1.05 for membrane potential (Berner, 1999;Chamberlin, 2004;Rogers et al, 2007;Trzcionka et al, 2008;Guderley and Seebacher, 2011). For all three species, the rates of mitochondrial proton leak were calculated at the highest common membrane potential value of 150 mV from the oxygen consumption rate by assuming a constant stoichiometry of six protons pumped (and leaked) per atom of oxygen for succinate.…”
Section: Mitochondrial Membrane Potentialmentioning
confidence: 99%
“…It is important to note that one previous study has reported a proton leak activity of around 30 nmol H + min −1 mg −1 protein in skeletal muscle mitochondria of common frog at 25°C (St-Pierre et al, 2000). Given that basal non-phosphorylating respiration rate and basal proton leak activity are on average 3.4-or 2.5-fold greater in skeletal muscle mitochondria than in liver mitochondria, respectively (St-Pierre et al, 2000;Hulbert et al, 2006;Rogers et al, 2007;Trzcionka et al, 2008;Guderley and Seebacher, 2011), the proton leak activity value of liver mitochondria from common frog should have ranged from 14 to 8.7 nmol H + min −1 mg −1 protein (at 150 mV and 25°C). Hence, in the present study, the calculated mean value of 9.7±1.2 nmol H + min −1 mg −1 protein (Fig.…”
Section: Mitochondrial Membrane Potentialmentioning
confidence: 99%